PENGARUH KEPRIBADIAN TERHADAP KINERJA KARYAWAN BERPENDIDIKAN TINGGI: ANALISIS PADA PERUSAHAAN PETERNAKAN DI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA - Ratna Widyasari; Suci Paramitasari Syahlani; Krishna Agung Santosa (KINERJA, 2007)
The objective of this research is to identify the personal ity effect on job performance of high educational level staff in companies of livestock industry. Survey design was used in this study. Thirty respondents were selected by using purposive sampl ing method; those were the ones who worked in companies of l ivestock industry, had at least diploma degree and had working experience 3-15 years. Data was col lected by individual interviews. Jackson Personal ity Index was used to measure personal ity variable and Workplace Behavior Questionnaire for perceptual measurement of job performance. Data was analyzed by using regression analysis. The result shows that regression coefficient was 0,64, R2 33,40% and significance level was 0,014. This result indicates that personal ity affect positively and significantly in order to develop job performance. Therefore, personality aspect should be included in recruitment process of high educational level staff.Keywords : personality, job performance, livestock, poultry industry